Sosialisasi Program Latihan Motor Ablity Kepada Asisten Pelatih Dojo Lembaga Karate-Do Indonesia Se-Kecamatan Koto Tangah - Arie Asnaldi; kibadra Kibadra (Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Uiveristas Negeri Padang Jl. Prof. Hamka, Air Tawar Padang 25131 Telp. 0751-7059901, 2019)
The role of a Dojo trainer in directing karateka to be able to achieve the things mentioned above, the City of Padang has many Dojo including the Dojo Angkasa Lanud Padang. Dojo in the general sense is a training ground. According to Wahid (2007: 8) Dojo which means